Personnages dans l'espace, Personnages comme espace: une analyse du conte Â« Barbe Bleue Â» par Charles Perrault et les révisions de Tahar Ben Jelloun et d'Amélie Nothomb,Characters in space, Characters as space: an analysis of 'Bluebeard' by Charles Perrault and revisions by Tahar Ben Jelloun and Amélie Nothomb - Jimu, Kundai Michelle (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
Dans un couple, la négociation de l'espace domestique est contesté. Dans le conte Â« La Barbe Bleue Â» (1697) de Charles Perrault, cette négociation de l'espace est particulièrement dangereuse. Le mari a un espace privé Ã  lui, interdite Ã  sa femme, dans lequel il cache un secret sinistre : il a tué toutes les épouses précédentes. L'existence de cette pièce menace l'équilibre du foyer, mettant en question le droit Ã  un espace privé, et révélant le danger de garder un secret quand on vit en couple. Quand l'épouse franchit le seuil de la pièce interdite, son mari se met en colère et s'apprÃªte Ã  la tuer. Il s'ensuit une lutte acharnée entre homme et femme, devenus adversaires. Puisque la chambre interdite joue un rÃ´le capital dans ce récit, cela suggère que les éléments spatiaux jouent un rÃ´le significatif au sein du couple. Alors, on vise Ã  analyser le cadre domestique et son rÃ´le dans le rapport entre les personnages. Avant leur mariage, l'épouse avait déjÃ  une idée que Barbe Bleue n'était pas honorable, ce qui remet en question sa décision d'épouser cet homme. Au mÃªme temps, on se demande pourquoi l'époux aurait tué toutes les épouses précédentes. Cela incite le lecteur Ã  chercher Ã  mieux comprendre les personnages. A cette fin, on vise Ã  considérer les personnages comme des espaces, eux aussi, ce qui permettra une analyse approfondie de leur caractère et de leurs rapports personnels. Nous ferons la comparaison du conte perraultien avec les versions contemporaines de notre époque de Tahar Ben Jelloun et d'Amélie Nothomb. Dans la version jellounienne, l'intrigue se déroule dans un cadre musulman et maghrébin, tandis que le récit nothombien se situe Ã  Paris. Ces ouvrages présentent donc des perspectives neuves sur Barbe Bleue et sa dernière épouse, et sur le cadre dans lequel ils se trouvent.,For a couple, negotiating the spatial dynamics of their home can be a challenging feat. In the story of "Bluebeard" (1697) by Charles Perrault, this negotiation is presented in an even more grim light. The husband sets aside a private room for himself, off-limits to his wife, in which he conceals a deadly secret, that he has murdered his previous wives. The very existence of this forbidden chamber threatens the stability of the household and raises the question about whether secret unshared spaces between partners are tenable, and indeed whether spouses have the right to keep secrets. When the wife enters this forbidden room and discovers the corpses of his previous wives she provokes the anger of her husband, who then attempts to kill her as punishment. A fierce struggle ensues between husband and wife, who have now become adversaries. Because the forbidden chamber plays a key role in this story, this tells us that space is very important to the relationship between the couple. Thus, we intend to explore the domestic sphere and its role in the relationship between the characters. Prior to their marriage, the wife already has an indication as to her husband's dubious character, which calls into question her decision to marry him. We also wonder why Bluebeard might have murdered his previous wives. To understand them better, the characters will be considered as spaces, an approach which has the potential to offer a deeper and more holistic analysis of their characters and their personal relationships. We will be comparing Perrault's tale to two revisions by Tahar Ben Jelloun and Amélie Nothomb, which place the story into different contexts: the Islamic world and modern-day Paris respectively. These two revisions provide interesting and new perspectives on the couple in the domestic space and the ways in which the characters are represented.
Keywords: Perrault, Charles, 1628-1703 -- Barbe bleue; Perrault, Charles, 1628-1703 -- Criticism and interpretation; Fairy tales -- Psychological aspects; Space; Characters and characteristics in literature; Ben Jelloun, Tahar, 1947- -- Criticism and interpretation; Nothomb, AmeÌ lie -- Criticism and interpretation